Caspases and p53 Modulate FOXO3A/Id1 Signaling During Mouse Neural Stem Cell Differentiation - Aranha, Marcia M. (2015)
Neural stem cells (NSCs) differentiate into neurons and glia, and a large percentage undergoes apoptosis. The engagement and activity of apoptotic pathways may favor either cell death or differentiation. In addition, Akt represses differentiation by up-regulating the inhibitor of differentiation 1 (Id 1), through phosphorylation of its repressor FOXO3A. The aim of this study was to investigate the potential cross-talk between apoptosis and proliferation during mouse NSC differentiation. We determined the time of neurogenesis and gliogenesis using neuronal beta-III tubulin and astroglial GFAP to confirm that both processes occurred at similar to 3 and 8 days, respectively. p-Akt, p-FOXO3A, and Id 1 were significantly reduced throughout differentiation. Caspase-3 processing, p53 phosphorylation, and p53 transcriptional activation increased at 3 days of differentiation, with no evidence of apoptosis. Importantly, in cells exposed to the pancaspase inhibitor z-VAD.fmk, p-FOXO3A and Id 1 were no longer down-regulated, p53 phosphorylation and transcriptional activation were reduced, while neurogenesis and gliogenesis were significantly delayed. The effect of siRNA-mediated silencing of p53 on FOXO3A/Id 1 was similar to that of z-VAD.fmk only at 3 days of differentiation. Interestingly, caspase inhibition further increased the effect of p53 knockdown during neurogenesis. In conclusion, apoptosis-associated factors such as caspases and p53 temporally modulate FOXO3A/Id 1 signaling and differentiation of mouse NSCs. J. Cell. Biochem. 107: 748-758, 2009. (C) 2009 Wiley-Liss, Inc.. - Fundacao para a Ciencia e a Tecnologia (FCT) ; FEDER [PTDC/SAU-FCF/67912/2006]. - Fundacao para a Ciencia e a Tecnologia (FCT) and FEDER; Grant number: PTDC/SAU-FCF/67912/2006.